(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The peculiarities of the N-imidazole sorption on the smooth platinum electrode have been studied in the 0–3.0 V potentials range by means of the fast potentiodinamic impulses method. The two characteristic fields of the sorption have been observed for imidazole: the first – destructive sorption field on the namely platinum electrode within the 0–1.25 V potentials range (maximal values under 0.4 V), and sorption on the PtO2 oxide layer under higher anodic potentials (maximal values under 2.3 V).